Learning to Write Short Stories with the Assistance of Social Media as a Means of Improving Students Writing Skills in Indonesian Language Subjects Class XI SMA/SMK/MA - Arief Rachman Hadi; Elmustian Elmustian; Hasnah Faizah; Cipto Hadi (Universitas Cokroaminoto Palopo, 2025)
This research aims to enhance the short story writing skills of class XI SMA/SMK/MA students by utilizing the Telegram Bot as an innovative learning medium. Writing short stories is a fundamental skill in Indonesian language learning but often encounters challenges due to low student interest and limited innovation in instructional methods. This study employed a case study method with a qualitative approach to explore the application of Telegram Bots in improving students' writing skills. Data were collected through observation, interviews, and questionnaires, and analyzed to assess students' writing abilities, creative thinking, and engagement with social media. The findings indicate that the use of Telegram Bots significantly enhances students' proficiency in story structure and language use. Furthermore, social media has proven effective in motivating students by providing inspiration, fostering creative discussions, and facilitating constructive feedback. This research demonstrates that technology-based innovations, such as Telegram Bots, can create interactive, effective, and contextually relevant learning experiences tailored to the demands of the digital era.